Reação reversa atípica em paciente com hanseníase dimorfa co-infectado pelo HIV Atypical reversal reaction in a borderline leprosy patient co-infected with HIV - Rafaela de Lima Caruso; Renata Martins Fernandes; Márcio Soares Serra; Ricardo Barbosa Lima; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2007)
A infecção pelo HIV não altera a história natural da hanseníase. Observa-se maior incidência de estados reacionais nos pacientes co-infectados, além de casos mais graves de neurite. Paciente soropositiva com hanseníase dimorfa tuberculóide manifestou reação reversa exuberante. Lesões cutâneas atípicas e raras surgiram após a introdução da terapia anti-retroviral que promoveu o início da recuperação imunológica com aumento de linfócitos T CD4+ e queda da carga viral. A restauração da imunidade celular nos pacientes soropositivos pode precipitar reações reversas, descritas recentemente como uma das manifestações da síndrome inflamatória de reconstituição imunológica associada à hanseníase. HIV infection does not modify the natural course of leprosy. However, HIV co-infection seems to be associated with an increased rate of reactional states and more severe cases of neuritis. The authors describe a case of borderline tuberculoid leprosy in a HIV-positive patient who developed a marked reversal reaction. Atypical and rare skin manifestations, such as verrucous lesions and ulcers, appeared after highly active antiretroviral therapy, which resulted in increased CD4+ T-lymphocyte count and drop in viral load. The restoration of the cellular immunity in HIV-seropositive patients can trigger reversal reactions that are one of the manifestations of the immune reconstitution inflammatory syndrome. Only recently the syndrome has been associated with leprosy.